'Rise up and walk!' The Church of Sweden and the 'problem of vagrancy' in the early twentieth century. (15th March 2022) - Al Fakir, Ida
ABSTRACT: The article examines how people within the Church of Sweden's leadership tried to solve 'the problem of vagrancy' in Sweden in the early twentieth century. In focus are the priest John Melander and the deacon Josef Flinth, who advocated and realized various activities for categories of poor and mobile men in the population. These interventions, defined as help-to-self-help, differentiated between the 'worthy' and the 'unworthy' needy. In publications and lectures, Melander and Flinth presented arguments to transfer 'unworthy' categories to the 'worthy', thereby expanding the community of value . This expansion was conditioned, however, by boundaries drawn regarding ideas on belonging and ethnicity. Working in the borderlands of the community as part of a Christian calling, Melander and Flinth contributed to the expansion of social work in the early twentieth century.